1993
DOI: 10.1111/j.1750-3639.1993.tb00720.x
|View full text |Cite
|
Sign up to set email alerts
|

Microglial Reaction in the Rat Cerebral Cortex Induced by Cortical Spreading Depression

Abstract: The response of microglial cells to cortical spreading depression (CSD) was studied in rat brain by immunocytochemistry. CSD was elicited for one hour by the topical application of 4M potassium chloride solution and the microglial reaction examined immunocytochemically after 4, 16, 24 and 72 hours. CSD was sufficient to induce a microglial reaction throughout the cortex at 24 hours. Activated microglial cells furthermore showed a striking de-novo expression of major histocompatibility complex class II antigens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(72 citation statements)
references
References 24 publications
5
67
0
Order By: Relevance
“…2) (Duchen, 1992). Furthermore, SD in vivo activates astrocytes (Kraig, et al, 1991) and microglia (Caggiano and Kraig, 1996;Gehrman et al, 1993). In parallel with these in vivo glial changes, SD in HOTCs similarly triggered astrocytes and microglia to show evidence of activation.…”
Section: Cellular Responses Of Hotcs To Spreading Depressionmentioning
confidence: 88%
See 1 more Smart Citation
“…2) (Duchen, 1992). Furthermore, SD in vivo activates astrocytes (Kraig, et al, 1991) and microglia (Caggiano and Kraig, 1996;Gehrman et al, 1993). In parallel with these in vivo glial changes, SD in HOTCs similarly triggered astrocytes and microglia to show evidence of activation.…”
Section: Cellular Responses Of Hotcs To Spreading Depressionmentioning
confidence: 88%
“…In addition, we performed labeling studies with the microglial marker OX-42 to determine if SD in HOTCs induced activation of microglia similar to that seen in vivo (Caggiano and Kraig, 1996;Gehrman et al, 1993). In normal HOTCs, OX-42 positive microglia typically displayed a small soma from which extended numerous finely branched processes (Fig.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…3) eicosanoids and anti-inflammatory drugs function in normal and pathologic brain tissue processes. Microglia are activated by diverse stimuli, including nerve transection (Graeber et al, 1988a,b;Morioka and Streit, 1991)) various neurological diseases (for review, see McGeer et al, 1993), and even a noninjurious stimulus, such as spreading depression (Gehrmann et al, 1993;, which may be associated with migraine headache (Moskowitz et al, 1993). In vitro stimuli, such as y-interferon (Wong et al, 1984) and LPS (Hetier et al, 1988), also activate microglia causing them to produce IL-l (Hetier et al, 1988) and tumor necrosis factor (Sawada et al, 1989)) alter expression of surface molecules (Imamura et al, 1991) , and enhance their NO production (Zielasek et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…An early study has shown that injection of 4 M KCl into the cortex induced cortical SD. The SD induced by KCl was sufficient to activate microglial cells and resulted in morphological changes, an index for activation of microglial cells (81). Later, a report showed that an increase in the concentration of K + ions in the culture medium significantly augmented LPS-stimulated NO and TNF- production by mixed glial cells or isolated microglial cells (82).…”
Section: Increase In Extracellular Potassium Ionsmentioning
confidence: 98%